Psychological wellbeing among carers of children and adolescents with physical disabilities in North-Eastern Tanzania-a cross-sectional survey study - Elia Asanterabi Swai; Elia Asanterabi Swai; Elia Asanterabi Swai; Haleluya Imanueli Moshi; Haleluya Imanueli Moshi; Sia Emmanueli Msuya; Sia Emmanueli Msuya; Sia Emmanueli Msuya; Ann Sörlin; Klas-Göran Sahlen; Marie Lindkvist (Frontiers Media S.A., 2024)
IntroductionCaring for physically disabled children, particularly in contexts where resources are often insufficient or absent, exposes primary carers to significant psychological strain. The lack of structured mechanisms to address this psychological burden poses a considerable threat to the wellbeing of both carers and the children with disabilities under their care. However, research on the psychological wellbeing of carers in Tanzania is scarce. This study aimed to evaluate the psychological wellbeing and symptoms of anxiety and depression, along with associated factors, of carers of children, and adolescents with physical disabilities in the Kilimanjaro region.MethodsA cross-sectional survey was conducted from November 2020 to June 2021 in the Kilimanjaro region, involving 212 carers. The Swahili versions of the WHO-5 Wellbeing Index and Hopkins Symptoms Check List-25 were used to assess psychological wellbeing and symptoms of anxiety and depression. Data were analysed using IBM SPSS Statistics V.28. Multivariable linear and binary logistic regression were used to assess the associations.ResultsMore than four fifths (81%) of the carers were parents, and most of these parents were mothers (92%). Of the 212 carers, more than half (51%) exhibited poor psychological wellbeing, 42% had symptoms of anxiety, and 38% symptoms of depression. Notably, poor psychological wellbeing was significantly associated with symptoms of anxiety and depression. Results of a multivariable regression analysis indicated that extended family support was associated with better psychological wellbeing and lower odds of symptoms of anxiety and depression. A higher estimated monthly income was associated with better psychological wellbeing, and lower odds of symptoms of depression. Access to rehabilitation for the child was associated with improved psychological wellbeing and decreased likelihood of symptoms of anxiety.ConclusionMany carers of children, and adolescents with physical disabilities in Tanzania are at high risk of having poor psychological wellbeing, and symptoms of anxiety and depression. Support from extended-family networks is crucial in promoting good psychological wellbeing. The government in Tanzania should improve rehabilitation services, especially in disadvantaged rural areas, and integrate mental-health screening for carers in both rehabilitation programmes and primary healthcare.